Inquiring into Emerging Understandings of Physical Literacy Through Interactivity - Martinez Mora, Laura (Université d'Ottawa / University of Ottawa, 2021)
This thesis is comprised of two articles, bookended an introductory chapter and a closing chapter. The first article is called “Are We Heading in the Right Direction?: An Attribute Analysis of Physical Literacy Assessment Tools” and the second one “Physical Literacy, Interactivity, and Communication: Emergent Teacher Understandings.” This is a viewpoint that analyzes what attributes of physical literacy (Whitehead, 2010; 2019), were exemplified or overlooked in three Canadian physical literacy assessment tools used by teachers, coaches, parents, and students. The analyzed tools included the Canadian Assessment of Physical Literacy (CAPL) developed by the Healthy Active Living and Obesity (HALO) Research Group, PlayTools: Play Fun developed by Sport for Life (S4L), and Passport for Life developed by Physical and Health Education (PHE) Canada. In conclusion, all three tools included assessments of Motivation, Confidence, Competence, Awareness, and Understanding. However, only Passport for Life assessed all of Whitehead’s (2019) attributes yet, not in equal amounts. The second article aimed at describing the emergent understandings of the concept of physical literacy from the perspective of new and seasoned teachers interested in PE. By means of the exploration, recollection, and description of a vivid interactive and relationally oriented pedagogical physical activity understandings of physical literacy were described. Motion-sensing phenomenological interviews with three participants were carried out to better understand what the concept of physical literacy meant in their everyday practice. Recommendations for future research were that more attention could be placed on the least developed aspects of physical literacy, bodily communication and the role it plays in forming relational connections between students and teachers.
Keywords: physical literacy; movement; assessment; phenomenology; interactivity; curriculum